Validation of Levels of Decorin as A Reliable Biomarker of Osteoarthritis: Comparison of Serum and Synovial Fluid Levels - Rizwan Anwar, Bilal Habib, Yasir Mustafa, Asma Kazi, Omer Farooq, Mufassar Nishat (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The proteoglycan decorin, which plays an important part in the aetiology of osteoarthritis as well as a role in the binding of collagen, was the focus of this study’s background information and objectives (OA). This investigation was carried out with the objectives of determining the levels of decorin in the blood and synovial fluid of patients who suffered from knee OA and determining whether or not these levels had a correlation with OA and the Western Ontario and McMaster Universities Osteoarthritis (WOMAC) score. Place of Study: Islam medical college Sialkot Duration: December 2021 to May 2022 Methods: In this prospective study, a total of 60 persons were enrolled in the study and control groups: 30 people with knee osteoarthritis and 30 people with other knee sjoint problems. For the purpose of determining how well the knee functions, the WOMAC score was utilised.Both the levels of decorin in the blood and the levels of decorin in the synovial fluid were analysed by means of an enzyme-linked immunosorbent assay (ELISA). We used a technique known as binary logistic regression, which contained both a single and a multi-categorical predictor, in order to evaluate the potential risk factors for OA. This allowed us to determine which characteristics would increase the likelihood of developing OA. Results: It was discovered that the levels of serum decorin in the group that was diagnosed with OA were statistically and considerably higher than the levels found in the group that acted as the control (P 0.001). There was not a significant difference in the amounts of decorin found in synovial fluid between those who had OA and the control group. WOMAC score (OR)=1.073, 95% confidence interval (CI): 1.032-1.116, P<0 .001 This association between OA and high serum decorin levels was shown to be statistically significant (OR=1.114, 95%CI: 1.030–1.205, P=0.007). OA was demonstrated to be strongly linked with high serum decorin levels. There was shown to be a positive association between the levels of serum decorin and the WOMAC score in patients who had OA. Conclusions: An increase in serum decorin levels may be indicative of changes in the structure of the extracellular matrix.The fact that there is a positive connection between the serum decorin level and the WOMAC score lends credence to the previous assertion that this conclusion is correct. It was found that having a higher WOMAC score and having higher serum decorin levels are both risk factors associated with osteoarthritis (OA). On the other hand, there was no link found between osteoarthritis and the amount of decorin found in the joint fluid.